Williams Syndrome, Human Self-Domestication, and Language Evolution - Niego, Amy; Benítez-Burraco, Antonio (Frontiers in Psychology, 2019)
Language evolution resulted from changes in our biology, behavior, and culture. One source of these changes might be human self-domestication. Williams syndrome (WS) is a clinical condition with a clearly defined genetic basis and resulting in a distinctive behavioral and cognitive profile, including enhanced sociability. In this paper we show evidence that the WS phenotype can be satisfactorily construed as a hyper-domesticated human phenotype, plausibly resulting from the effect of the WS hemydeletion on selected candidates for domestication and neural crest function. Specifically, we show that genes involved in animal domestication and neural crest development and function are significantly dysregulated in the blood of subjects with WS. We also discuss the consequences of this link between domestication and WS for our current understanding of language evolution.